Medical education during the COVID -19 pandemic: global initiatives for undergraduate, internship, and medical residency - Herrera-Añazco, Percy (2020)
The 2019 coronavirus disease pandemic (COVID-19) has posed various challenges to the strata of society and medical education has been no exception. Globally, universities have proposed various initiatives in undergraduate and medical internships such as the partial virtualization of their curricular content, the modification of their curriculum and educational activities and the incorporation of students from the last years to the management of COVID-19 patients. In medical residency, surgical specialties and those that base their learning on procedures are the most affected. Residents of different specialties have been incorporated into healthcare tasks different from their specialty and some of their learning activities have been virtualized. Peru must make an evaluation of these strategies and the possible adaptation to our reality.